Legitimate targets?: social construction, international law and US bombing - Dill, Janina (Cambridge studies in international relations, 2015)
"Based on an innovative theory of international law, Janina Dill's book investigates the effectiveness of international humanitarian law (IHL) in regulating the conduct of warfare. Through a comprehensive examination of the IHL defining a legitimate target of attack, Dill reveals a controversy among legal and military professionals about the 'logic' according to which belligerents ought to balance humanitarian and military imperatives: the logics of sufficiency or efficiency. Law prescribes the former, but increased recourse to IL in US air warfare has led to targeting in accordance with the logic of efficiency"--